Overhead Allocation via Mathematical Programming Models. - Kaplan, Robert S.; Thompson, Gerald L. (The Accounting Review, 1971)
In this paper we have devised methods for allocating overhead, charges on the basis of mathematical programming models of the firm's production and sales possibilities. The basic scheme was to charge products on the basis of their utilization of the scarce resources of the firm. The prices for use of these resources were obtained from the dual variables associated with the constraints of profit-maximizing programming models. Special attention was given to traceable and avoidable overhead and overhead subsidies that arise because of sales and production interdependencies or managerial constraints. Our objective, in all of these procedures, has been to devise a method for allocating overhead that does not distort the relative profitability of products so that managers would make identical product related decisions both before and after the overhead allocation. As such, the method captures a principal benefit of direct costing analysis while significantly extending this benefit to recognize scarce resource utilization and interaction with other products in reporting profitability. At the same time, the method avoids a difficulty of direct costing systems in that it is a full costing system with all overhead being allocated to products. Also the availability of the original programming model (before any overhead allocations) facilitates marginal analysis for short term product related decisions and expansion of scarce resources.